Guided Inquiry Learning Model in Chemistry Education: A Systematic Review - Robiatul Adauyah; Nurfina Aznam (Jurnal Penelitian Pendidikan IPA, 2024)
The abstractness of chemical concepts can be understood easily through learning chemistry using guided inquiry. This article uses the Systematic Literature Review (SLR) method to review eleven articles published from 2018 to 2023. Articles were systematically obtained from the online article databases ERIC, Scopus, and Google Schloar. The purpose of the review is to provide information to teachers and researchers in the field of chemistry education about the definition of guided inquiry models, the effect of guided inquiry models on chemistry learning outcomes, and how to apply guided inquiry models/strategies in chemistry learning. The review results show that the definition of various guided inquiry models involves students into a problem and confronts students with an investigation, and directs students to solve the problem of the problem. The effects of guided inquiry models on chemistry learning outcomes include improving metacognition, concept understanding, critical thinking skills, science process skills, learning outcomes, and creative thinking skills. Various chemistry learning models have also been applied in several learning models or strategies such as Guided Inquiry, Guided Inquiry-Based on Blended Learning, Flipped Classroom Based on Guided Inquiry Learning, Guided Inquiry Model Integrated with STEM, Guided Inquiry and Task Hierarchy Analysis Model in Cooperative Learning Strategy